KINERJA MODAL SOSIAL DALAM KAITANNYA DENGAN PENDAPATAN MASYARAKAT AGROFORESTRY: STUDI DI DESA KARANG REJO KECAMATAN JATI AGUNG LAMPUNG SELATAN - Samsul Bakri; Rommy Qurniati; Rahmat Safe’i; Rudi Hilmanto (Lambung Mangkurat University-Indonesia, 2021)
Social capital of agroforestry’s community needs to be developed to enhance their productivity. It is because the physical capital has generally been very intensively utilized, as in Karang Rejo Village, Jati Agung Subdistrict, South Lampung Regency. This study aims to model [1] Total household income [Y-tot] as the function of 5 groups of variables (demographics, sources of income from other sectors, physical capital, social capital and access to information, and to model [2] the network as function of accessibility to information. A survey of 25 households was conducted in August 2019, to collect data of total income, demographics, physical capital (land tenure, ownership of motorbikes, cattle, goats, and chickens), accessibility (to cultivated land, to the village center, and to sub-districts), social capital performance (norm strength, trust, and network), access to information (participation in extension, watching TV habits, and cellphone signal strength). The ordinary least square was applied to build both for the Model [1] and Model [2]. The results showed that: [1] The total income [Y-Tot] can significantly be increased through the addition of physical capital as well as access to information (especially participation in extension), and [2] The elements of social network capital can be developed through the use of motorbikes, increasing community participation in extention, and reducing the frequency of watching TV.